Addiction Analysis of Online Games and Implications With Islamic Guidance and Counseling: Career Counseling - Romi Fajar Tanjung (Konseling Religi: Jurnal Bimbingan Konseling Islam, 2019)
The industrial revolution 4.0 developments very sophisticated technology. The technology makes it easy to affairs of human life so that all activities be fast and instant. The use of appropriate technology will provide a positive impact on human beings, on the contrary the use of technology that is poorly controlled and redundant will have negative impacts for humans, especially for adolescents. One form of the use of technology that can be bad for adolescents, if carried to excess use such as playing online games. Play online games excessively and without control could damage the lives of adolescents, including the attitudes and behavior more specific daily impact on the journey and career planning adolescents. Therefore, to prevent and cope with things that are not desirable need intervention for problem handling the online game addiction among adolescents. One recommendation in the handling of the problem of online game addiction among adolescents is Islamic guidance and counseling: career counseling. This research method using mixed methods. The research sample is early adolescents, amounting to as many as 113 people. Data analysis using descriptive and quantitative analysis. Islamic guidance and counseling: career counseling can be utilized for the handling of online game addiction among adolescents, so as not to adversely affect the journey and career planning adolescents.